Serum antioxidant status in Iraqi women with endometrial cancer - Al- Ruba,ei, Salwa H. N.; Jasim, Rana K.; Al-Rawaq, Khudhair J. S. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Endometrial cancer is the most common gynecologic malignancy in the United States and the fourth most common cancer in women, comprising 6% of female cancers. Objectives: The aim of this study is to investigate the antioxidant vitamins, Coenzyme Q10 and oxidative stress in patients with endometrial cancer. Patients and methods: Fifty six endometrial cancer women patients with various clinical stages (stage 1A, stage1B, stage II, stage III, stage IV) mean aged 58.055 ± 10.561 years, and 30 healthy women volunteers mean aged 39.731 ± 13.504 years, were includes as control group. Results: The results in this study revealed a highly significant decreased (P<0.01) in β- carotene, Vitamin E and significant increased (P<0.01) in (Uric acid and MDA). The results of ( Coenzyme Q10 and Vitamins (A, C) showed a significant decreased (P<0.05), in the sera levels of patients with endometrial cancer as compared to control group. Conclusions: This study suggest that high levels of oxidative stress and low levels of antioxidant defense system may be associated with increased the risks of endometrial cancer.